Do male engagement and couples' communication influence maternal health care-seeking? Findings from a household survey in Mozambique - Gilda G. Sitefane; Joya Banerjee; Diwakar Mohan; Connie S. Lee; Jim Ricca; Myra L. Betron; Rosa Marlene Manjate Cuco (BMC, 2020)
Abstract Background This study explored effects of couples' communication and male participation in birth preparedness and complication readiness (BPCR) on delivery in a health facility ("institutional delivery"). A cross-sectional, baseline household survey was conducted in November 2016 prior to an integrated maternal and child health project in Nampula and Sofala Provinces in Mozambique. Methods The study used the Knowledge, Practices and Coverage survey tool, a condensed version of the Demographic and Health Survey and other tools. The sample included 1422 women. Multivariable logit regression models tested the association of institutional delivery with couples' communication and four elements of BPCR both with and without male partners: 1) saving money, 2) arranging transport, 3) choosing a birth companion, and 4) choosing a delivery site; controlling for partners' attendance in antenatal care and social and demographic determinants (education, wealth, urban/rural location, and province). Results The odds that women would deliver in a health facility were 46% greater (adjusted odds ratio (aOR) = 1.46, 95% confidence interval (CI) = 1.02-2.10, p = 0.04) amongst women who discussed family planning with their partners than those who did not. Approximately half of this effect was mediated through BPCR. When a woman arranged transport on her own, there was no significant increase in institutional delivery, but with partner involvement, there was a larger, significant association (aOR = 4.31, 2.64-7.02). Similarly, when a woman chose a delivery site on her own, there was no significant association with institutional delivery (aOR 1.52,0.81-2.83), but with her partner, there was a larger and significant association (aOR 1.98, 1.16-3.36). Neither saving money nor choosing a birth companion showed a significant association with institutional delivery-with or without partner involvement. The odds of delivering in a facility were 28% less amongst poor women whose partners did not participate in BPCR than wealthy women, but when partners helped choose a place of delivery and arrange transport, this gap was nearly eliminated. Conclusions Our findings add to growing global evidence that men play an important role in improving maternal and newborn health, particularly through BPCR, and that couples' communication is a key approach for promoting high-impact health behaviors.